(untitled) (Global Journal of Science Frontier Research, 2014)
Forests comprise an essential life support of the rural people of Ghana. This is particularly the case in the Ho Municipality area, as far as the provision of fertile land for food crop production, timber for housing, medicine, and creating suitable micro climates conducive for rainfall are concerned. Small scale industrial activities, trading and the services sector have recently expanded the scope of employment option in the Ho Municipality. The agricultural sector continues, however, to be a leading employer. Production pressure on forest cover in the area due to agriculture and related activities have accelerated deforestation, destroyed animal habitat and contributed to the loss of valuable tree species. While farmers are aware of accelerated forest cover loss, they do not have access to accurate data on the extent and rate of deforestation in order to understand deforestation dynamics to plan remedial measures. In view of the data gap, the study described here was designed to assess the nature, extent and rate of deforestation in the Ho Municipality in Ghana. Data analysis was undertaken by classifying Land sat images from 1975 to 2001 and through analysis of questionnaire data. Study results show loss of forest cover by 6562 hectares from 1975 to 1991, and a further loss of 2949 hectares from 1975 to 2001. It is evident that the accelerated pace of deforestation has negatively affected the biophysical environment.